PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN ROTI KAHANG JAYA DI KOTA KUPANG - Grendy Pandie; Thom W. A. Isliko (Journal of Management Small and Medium Enterprises (SMEs), 2017)
This study aims to determine the effect of Brand Image to Purchasing Decisions at Kahang Jaya Bakery. Themethod of analysis used is Descriptive Analysis, Validity, Reliability, Factor Analysis, Simple Linear AnalysisAnd Hypothesis Testing. The results of the Factor Analysis showed that the dimensions of the Type of BrandAssociation, Endorsement Brand Association, Brand Association Strength, Uniqueness of Brand Associationsand Purchase Decision to measure the value of KMO Measure of Sampling Adequacy are significant for allvalue <0.50, the measurement of the value of Research Variance Explained are all > 0.50 and ReliabilityConstruct of all the dimensions are CR> 0.70. Based on the analysis, it can be concluded that the Brand Imagewhich consists of : The Type of Brand Association, Endorsement Brand Association, Brand AssociationStrength And Uniqueness of The Brand Association has applied to the Kahang Jaya Bakery. Furthermore, theBrand Image of Kahang Jaya Bakery has an impact and a positive relationship to the Purchasing Decisionregression coefficient, significance f = 0.000. Results of determination coefficient (R2) showed that the effect ofthe Brand Image to Consumer Purchase Decision at Kahang Jaya Bakery by 90% and the remains of 10%influenced by other variables that was not discussed this research. It can be concluded that the Brand Image hasa strong influence on Consumer Buying Decision on Kahang Jaya Bakery.Keywords: Brand Image, Buying Decision.